Unevenly spatiotemporal distribution of urban excess warming in coastal Shanghai megacity, China: Roles of geophysical environment, ventilation and sea breezes. (1st May 2023) - Yang, Yuanjian; Guo, Min; Wang, Linlin; Zong, Lian; Liu, Duanyang; Zhang, Wenjie; Wang, Mengya; Wan, Bingcheng; Guo, Yide
Abstract: The complexity and uncertainty of urban excess warming are modulated by the morphology of urban areas, canopy urban heat island (CUHI)–heat wave interactions, the geographical–climatological background and the local circulation. Focusing on the coastal Shanghai megacity, we analyzed the synergistic effects of local climate zones (LCZs), urban ventilation, and sea breezes on the urban excess warming related to the CUHI and heat waves in summer from 2013 to 2018. Over the whole urban areas, the average CUHI intensity (CUHII) increased by 128.91% during heat waves periods relative to non-heat wave periods. Moreover, the spatial-temporal distributions of both CUHII and heat waves exhibited heterogeneously. In dense urban areas (e.g., LCZ 1 and 2), the blocking effect of dense high-rise buildings, and poor ventilation with low wind speeds would exacerbate urban excess warming, which exhibited relatively higher occurrence of heat waves and an increase in the CUHII. By contrast, over open areas of the urban periphery (eg., LCZ5), more heat wave events and stronger CUHII were mainly affected by the horizontal advective transport of urban heat at medium wind speeds. Particularly, the sea breezes could weaken the CUHII and decrease the occurrence frequency of heat wave events during daytime over coastal areas. In addition, the shading effects of high-rise buildings and the evaporative cooling effects of water and vegetation would also mitigate urban warming at the local scale, which would reduce the CUHII as well as the frequency of heat waves. Highlights: Urban excess warming related to the CUHI and heat waves has an unevenly spatiotemporal distribution. An urban surface transport index can effectively quantify urban heat transport by wind vector. Dense urban areas favor the high occurrence of heat waves and an increase in the CUHII. Open areas on the periphery of city are affected by the horizontal advection of urban heat. Sea breezes have a mitigating effect on the CUHII and heat waves in coastal urban areas.